(untitled) (Western European Journal of Linguistics and Education, 2024)
Well-known poetry belongs to lyrical works. Lyric (Greek "Lyra" is a musical instrument. This instrument was played while reciting verses) is a part of literature. There is an artistic image in the basis of any lyrical work. The artistic image is usually described as a form of the representation of reality and as a tool in art, the representation of abstract ideas in concrete forms of feeling. Metaphors are one of the main tools that provide imagery in poetry. Although all the words used interchangeably in terms of similarity form a type of metaphor, they are not all the same. We have mentioned that the problem of metaphor can be studied in many humanities fields besides literature. All these branches learn the metaphor in the aspect they are interested in, and divide it into groups based on the principle of classifications necessary for them. In modern linguistics, firstly they are divided into linguistic and poetic metaphors